Characterizing a Halo-Tolerant GH10 Xylanase from Roseithermus sacchariphilus Strain RA and Its CBM-Truncated Variant - Teo, Seng Chong; Liew, Kok Jun; Shamsir, Mohd Shahir; Chong, Chun Shiong; Bruce, Neil C.; Chan, Kok Gan; Goh, Kian Mau (MDPI, 2019)
A halo-thermophilic bacterium, Roseithermus sacchariphilus strain RA (previously known as Rhodothermaceae bacterium RA), was isolated from a hot spring in Langkawi, Malaysia. A complete genome analysis showed that the bacterium harbors 57 glycoside hydrolases (GHs), including a multi-domain xylanase (XynRA2). The full-length XynRA2 of 813 amino acids comprises a family 4_9 carbohydrate-binding module (CBM4_9), a family 10 glycoside hydrolase catalytic domain (GH10), and a C-terminal domain (CTD) for type IX secretion system (T9SS). This study aims to describe the biochemical properties of XynRA2 and the effects of CBM truncation on this xylanase. XynRA2 and its CBM-truncated variant (XynRA2ΔCBM) was expressed, purified, and characterized. The purified XynRA2 and XynRA2ΔCBM had an identical optimum temperature at 70 °C, but different optimum pHs of 8.5 and 6.0 respectively. Furthermore, XynRA2 retained 94% and 71% of activity at 4.0 M and 5.0 M NaCl respectively, whereas XynRA2ΔCBM showed a lower activity (79% and 54%). XynRA2 exhibited a turnover rate (kcat) of 24.8 s-1, but this was reduced by 40% for XynRA2ΔCBM. Both the xylanases hydrolyzed beechwood xylan predominantly into xylobiose, and oat-spelt xylan into a mixture of xylo-oligosaccharides (XOs). Collectively, this work suggested CBM4_9 of XynRA2 has a role in enzyme performance. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.